2008
DOI: 10.1103/physrevb.78.012405
|View full text |Cite
|
Sign up to set email alerts
|

Voltage-controlled surface magnetization of itinerant ferromagnetNi1xCux

Abstract: We argue that surface magnetization of a metallic ferromagnet can be turned on and off isothermally by an applied voltage. For this, the material's electron subsystem must be close enough to the boundary between para-and ferromagnetic regions on the electron density scale. For the 3d series, the boundary is between Ni and Cu, which makes their alloy a primary candidate. Using GinzburgLandau functional, which we build from Ni1-xCux empirical properties, ab-initio parameters of Ni and Cu, and orbital-free LSDA, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 16 publications
1
13
0
Order By: Relevance
“…A theoretical study of the effect of surface charge on the Curie temperature of ultrathin metallic films has been reported recently [124]. It was also predicted that it may be possible to induce a paramagnetic to FM phase transition at a metal surface (interface) by an applied electric field [125,126]. Very recently, it was demonstrated experimentally that by applying an electric field of approximately 10 MV cm −1 to a scanning tunnelling microscope (STM) tip above the Fe (001) surface 10 nm Fe islands can be switched from an AFM fcc to an FM bcc structure [127].…”
Section: (A) Interface Magnetizationmentioning
confidence: 99%
“…A theoretical study of the effect of surface charge on the Curie temperature of ultrathin metallic films has been reported recently [124]. It was also predicted that it may be possible to induce a paramagnetic to FM phase transition at a metal surface (interface) by an applied electric field [125,126]. Very recently, it was demonstrated experimentally that by applying an electric field of approximately 10 MV cm −1 to a scanning tunnelling microscope (STM) tip above the Fe (001) surface 10 nm Fe islands can be switched from an AFM fcc to an FM bcc structure [127].…”
Section: (A) Interface Magnetizationmentioning
confidence: 99%
“…Recently it was demonstrated that ME effect can be induced by free carriers 6 . In this case, due to spin-dependent screening 7 , an applied electric field produces an accumulation of spin-polarized electrons or holes at the metal-insulator interface resulting in a change of the interface magnetization 8 and the exchange splitting [9][10][11] .…”
mentioning
confidence: 99%
“…In this Rapid Communication we show that both arguments are actually misconceptions and a similar effect must exist in metals as recently predicted in Ref. 5. Its physical picture, however, is in a sense opposite of the conventional interpretation.…”
mentioning
confidence: 71%